2023
DOI: 10.1021/acs.est.3c04540
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Hydrogel Engineered Janus Membrane for Membrane Distillation with Robust Fouling, Wetting, and Scaling Resistance

Xin Yang,
Na Zhang,
Jiaojiao Zhang
et al.

Abstract: Membrane distillation (MD) is considered to be rather promising for high-salinity wastewater reclamation. However, its practical viability is seriously challenged by membrane wetting, fouling, and scaling issues arising from the complex components of hypersaline wastewater. It remains extremely difficult to overcome all three challenges at the same time. Herein, a nanocomposite hydrogel engineered Janus membrane has been facilely constructed for desired wetting/fouling/scaling-free properties, where a cellulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…As shown in Figures A and S10, all membranes sustained a stable flux (20.1–21.1 kg·m –2 ·h –1 ) along with near-perfect salt rejection during 12 h operation with a saline feed containing 100 ppm phenol, demonstrating that the addition of phenol did not induce membrane wetting. Besides, the introduction of the Alg/Al hydrogel layer did not adversely affect vapor flux of membrane, consistent with the results in previous studies. ,, The PTFE and P PTFE membranes exhibited low phenol rejection rates (below 10%) at various concentrations (Figure B), which indicated that the PDA/PEI layer made little contribution to phenol interception. The Alg/Al PTFE membrane displayed a sufficient phenol rejection efficiency of 99.52% with saline feed containing 100 ppm phenol, which was attributed to the Alg/Al layer.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Figures A and S10, all membranes sustained a stable flux (20.1–21.1 kg·m –2 ·h –1 ) along with near-perfect salt rejection during 12 h operation with a saline feed containing 100 ppm phenol, demonstrating that the addition of phenol did not induce membrane wetting. Besides, the introduction of the Alg/Al hydrogel layer did not adversely affect vapor flux of membrane, consistent with the results in previous studies. ,, The PTFE and P PTFE membranes exhibited low phenol rejection rates (below 10%) at various concentrations (Figure B), which indicated that the PDA/PEI layer made little contribution to phenol interception. The Alg/Al PTFE membrane displayed a sufficient phenol rejection efficiency of 99.52% with saline feed containing 100 ppm phenol, which was attributed to the Alg/Al layer.…”
Section: Resultssupporting
confidence: 90%
“…The Alg/Al hydrogel composite membrane was fabricated via sequential construction of Alg pregel and ionic crosslinking (Figure A). First, a polydopamine (PDA)/PEI hydrophilic layer was constructed on the hydrophobic PTFE membrane surface (denoted as P PTFE). , After that, 4 wt % Alg solution was uniformly coated on the P PTFE membrane by a casting knife followed by drying at room temperature (denoted as Alg PTFE). Finally, the Alg PTFE membrane was immersed in 0.5 M AlCl 3 solution for ionic crosslinking over 12 h. The resultant membrane (designated as Alg/Al PTFE) was thoroughly rinsed with DI water and stored in DI water until testing.…”
Section: Methodsmentioning
confidence: 99%
“…Photothermal materials, mainly including carbon-based nanomaterials (e.g., carbon nanotube), plasmonic nanoparticles (e.g., Au), semiconductors (e.g., metal oxide), and polymer materials (e.g., polydopamine), play a dominant role in the design of high-performance PMD membranes. Among them, an emerging 2D MXene family, especially transition titanium carbide (Ti 3 C 2 T x , T x = −F, −O, and −OH), has attracted great attention for solar water production with broad-band light absorption and superior light-to-heat conversion efficiency resulting from its localized surface plasmon resonance (LSPR) effect. Besides, the intrinsic hydrophilicity of Ti 3 C 2 T x nanosheets endowed them with desired antifouling property and good compatibility with hydroxyl-abundant materials via hydrogen bonding. , However, the utilization of Ti 3 C 2 T x in the design of a PMD membrane is limited and the performance needs to be further improved. , Our previous work demonstrates that a hydrogel composite Janus membrane exhibits a high vapor flux and robust fouling and wetting resistance when treating saline feed contaminated by oils and surfactants. , Inspired by the excellent photothermal conversion efficiency of MXene and antiwetting/antifouling property of functional hydrogels, the innovative combination of MXene with a hydrogel might be a feasible way to construct an advanced Janus PMD membrane, which has not been investigated yet.…”
Section: Design and Characterization Of The Hydrogel Composite Pmd Me...mentioning
confidence: 99%
“…For hypersaline water with complex components, low-surface-tension contaminants naturally accumulate and boost the concentration of contaminants at the liquid–vapor interface. This surface effect can easily induce membrane wetting. High salinity further exacerbates the surface effect because the presence of NaCl increases the affinity of low-surface-tension contaminants and accelerates the adsorption equilibrium process at the gas–liquid interface. , To avoid the contaminant accumulation, a hydrophilic layer with small pore size has been proposed to block the contaminants by size-seizing effect, forming a Janus membrane. However, small-sized solutes or organics easily get stuck in the pores of the hydrophilic layer. The strategy of blocking inevitably renders the membrane susceptible to issues such as scaling or fouling, particularly in hypersaline wastewater. , …”
mentioning
confidence: 99%